STUDENT PERCEPTIONS ON PARTS OF SPEECH AFTER TAKING INTEGRATED ENGLISH - Maili, Sjafty Nursitti NP; Ayu, Dewi Mutiara Indah; Sondari, Endang (Universitas Putera Batam, 2022)
This article discussed about perception students on parts of speech after taking Integrated English. The purpose of this research is to know the student’s perception about Parts of Speech such as noun, pronoun, verbs, adjective, adverb, preposition, conjunction and interjection. Problems is students still confuse to put words of parts of speech in a sentence, so the researcher wanted to know what is students’ perceptions on Parts of Speech after taking Integrated English. The method of this study is qualitative research which data was obtained with taking a note from WhatsApp. Michael Patton and Michael Cohran (2002,3) in Sihatul, M (2020) Qualitative research is characteristic by it is aim, which relate to understanding some aspects of social life, and it is methods which (in general) generate words, rather that numbers, as data for analysis. Based on the result of the research, the researchers found the students perception on the parts of speech; First, from ten students as taken data only five students got felt difficult to learn Parts of speech; Second, the students’ perception about Parts of Speech are Positive.